Altered ganglioside GD3 in HeLa cells might influence the cytotoxic abilities of NK cells - Wen-Chi Lee; Wen-Ling Lee; Wen-Yuann Shyong; Lin-Wei Yang; Min-Chun Ko; Chang-Ching Yeh; Shie-Liang Edmond Hsieh; Peng-Hui Wang (Elsevier, 2012)
Objective: Previously, we found that altered sialidases in HeLa cells in a natural killer-HeLa (NK-HeLa) coculture system contributed to the decreased cytotoxic ability of NK cells. However, changes that occur in the glycosylation of the HeLa cells in the NK-HeLa coculture system remain unknown. Materials and Methods: An NK-HeLa coculture system was used to examine the changes that occur in the gangliosides of HeLa cells. Results: GD3 expression in HeLa cells was significantly increased in the NK-HeLa coculture system. Exogenous ganglioside GD3 decreased the cytotoxic ability of the NK cells, which could be restored by the addition of the anti-GD3 antibody. Coadministration of GD3 and sialidase further decreased the cytotoxic ability of the NK cells, which could be partially restored by the addition of a sialidase inhibitor (DANA). GD3 expression in HeLa cells also decreased following DANA treatment. Conclusions: This study suggests that interactions between ganglioside GD3 and sialidases in HeLa cells influence the cytotoxic ability of NK cells.